The kind of friends we used to be - Dowell, Frances O'Roark. (New York : Atheneum Books for Young Readers, 2009)
Twelve-year-olds Kate and Marylin, friends since preschool, draw further apart as Marylin becomes involved in student government and cheerleading, while Kate wants to play guitar and write songs, and both develop unlikely friendships with other girls and boys.
Wilson's Children, October 2010.
Wilson's Junior High School, January 2010.
School Library Journal, March 2009.
Publisher's Weekly, December 2008.
Booklist, March 2009.
Horn Book, October 2009.
Keywords: Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; School stories; Best friends -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Schools -- Fiction